Wprowadzenie do rachunku kosztów działań w zakładach opieki zdrowotnej - Nieplowicz, Maria (The Introduction to the Activity Based Costing for Health Care Units, 2008)
The article prestnes the concept of the Activity Based Costing for health care units. The summary indicates the possible barrier of using the Activity Based Costing.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 298-305